2007
DOI: 10.1248/jhs.53.325
|View full text |Cite
|
Sign up to set email alerts
|

Clastogenicity of Quinoline and Monofluorinated Quinolines in Chinese Hamster Lung Cells

Abstract: Quinoline and four monofluorinated derivatives of quinoline (FQ's) were tested for their clastogenicity in a Chinese hamster lung (CHL) cell line using chromosomal aberration (CA) and micronucleus (MN) tests. Quinoline and all the fluoroquinolines, 3-, 5-, 6-, and 8-FQ, induced CA in the presence of the metabolic activation system. However, the clastogenic property was altered by fluorine-substitution. 3-FQ showed reduced cytotoxicity and clastogenicity. It was positive only at a higher dose than the other com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…According to Uno et al [ 60 ], quinoline derivatives does not induce the formation of micronucleus events in the bone marrow and gastrointestinal tract cells of rats. Similarly, for Suzuki et al [ 61 ], structural modifications in a quinoline derivative were unable to induce the formation of micronucleated lung fibroblast cells in the hamster. In opposition to these findings, antifungals used against candidiasis and dermatophytosis can induce severe mutagenicity in the cells of the patient.…”
Section: Resultsmentioning
confidence: 73%
“…According to Uno et al [ 60 ], quinoline derivatives does not induce the formation of micronucleus events in the bone marrow and gastrointestinal tract cells of rats. Similarly, for Suzuki et al [ 61 ], structural modifications in a quinoline derivative were unable to induce the formation of micronucleated lung fibroblast cells in the hamster. In opposition to these findings, antifungals used against candidiasis and dermatophytosis can induce severe mutagenicity in the cells of the patient.…”
Section: Resultsmentioning
confidence: 73%
“…The same effects for the 6-methylated and the parent quinoline were found by Debnath et al [37] . The latter substance was also shown to cause significant induction of liver micronuclei and chromosome aberrations in rats and the hamster lung fibroblast cell line CHL/IU [11] , [38] , [39] , [40] and is a potent hepatocarcinogen in mice and rats [41] , [42] , [43] . Indole was positive in the Ames assay [44] .…”
Section: Resultsmentioning
confidence: 99%
“…Different studies on the structure–genotoxicity relationship of Qs have shown that the incorporation of certain substituents in the Q core change their clastogenicity, mutagenicity, and carcinogenicity. For example, as indicated in Figure , a fluorine moiety incorporated at positions C‐5 and C‐7 of Q increases significantly its genotoxic activity; however, the incorporation at position C‐3 produces a complete reduction of its genotoxicity in different experimental models (LaVoie et al, ; Saeki et al, ,b; Miyata et al, ; Kato et al, ; Hakura et al, ; Suzuki et al, ). It has been also demonstrated that chlorine and fluorine incorporation at positions C‐2 and C‐3 of Q, respectively, result in the reduction of its carcinogenicity (Hirao et al, ; Saeki et al, ).…”
Section: Introductionmentioning
confidence: 99%